Methodology for mapping quantum and reversible circuits to IBM Q architectures - Almeida, Alexandre Araujo Amaral de (2019)
Research in the field of quantum circuits has increased as technology advances in the development of quantum computers. IBM offers access to quantum computers via the cloud service called IBM Q. However, these architectures have some restrictions regarding the types of quantum gates that can be realized. This work proposes a methodology for the mapping of quantum and reversible circuits to the architectures made available by the IBM Q project. The methodology consists in finding CNOT mappings using a set of defined qubits movements to satisfy the architectures constraints by adding as few gates as possible. In order to reduce the number of CNOT gates needing mapping, the permutation of the circuit can be changed. One alternative to find this permutation is trough exhaustive search. However, is not feasible as the number of qubit increases. To solve this problem, the permutation problem was formulated as an Integer Linear Programming problem. The mapping of quantum circuits realized with non-implementable gates and reversible Toffoli circuits to the IBM quantum architectures were proposed in this work as well. This was done by adapting the developed CNOT mappings along with the Integer Linear Programming formulation. The proposed methodology was evaluated by mapping quantum and reversible circuits to an IBM quantum architectures with 5 and 16 qubits. The results were compared with two algorithms that map quantum circuits to IBM architectures. The cost metric used in the evaluation were the number of quantum gates and the number of levels (depth) of the circuits. Experimental results have shown that the proposed methodology outperforms the other approaches regarding the circuits' size. The results of the methodology used to implement quantum (with non-implementable gates) and Toffoli circuits to IBM architectures have shown that the mapping targeting a specific architecture constraints results in a smaller mapped circuit. The methodology developed can be easily adapted to any quantum architecture. Also, the proposed Integer Linear Programming formulation can be used in any reversible circuit and can be applied in other research areas.